Evaluating treatment strategies for non–small cell lung cancer during COVID-19: A propensity score matching analysis. Issue 32 (12th August 2022) - Yu, Minhao; Cheng, Yalin; Zhang, Renfei; Wen, Tao; Huai, Sitao; Wei, Xiubo; Zhang, Liming
Abstract : We employed pandemic treatment strategies that we developed at the beginning of the coronavirus disease 2019 (COVID-19) pandemic, and it was not clear whether any adverse results were associated with our strategies. Therefore, we carried out a retrospective study to compare our pandemic treatment strategies with prepandemic protocols to determine whether the strategies used during the high-risk period of COVID-19 were appropriate. The observation period was September 2019 to February 2020. Patients hospitalized from December 2019 to February 2020 were included as an experimental group, and individuals hospitalized from September 2019 to November 2019 were included as a control group. All non–small cell lung cancer patients hospitalized during the observation period were included except for pediatric and obstetric patients, patients younger than 18 years old, and patients admitted only for routine follow-up examinations. Treatment strategies were evaluated based on the prognosis of the different treatment methods, including surgical and nonsurgical treatments and discontinuation of therapy. Survival curves were analyzed using the Kaplan–Meier method. Cox regression analysis was used for multivariate analysis of risk factors for progress-free survival. Propensity score matching was used for clinical characteristics to adjust for selection bias. Therapy discontinuation in the experimental group was significantly higher than in the control group ( P < .001). The differences in cancer progression and the number of deaths between the 2 groups were not significant ( P = .38 and .13, respectively). For late-stage patients, there were significant differences in nonsurgical treatment and discontinued therapy ( P < .001 and < .001, respectively) between the 2 groups, while the cancer progression and death toll differences were not significant ( P = .20 and .20, respectively). For early-stage patients, the differences in surgical treatment, discontinued therapy, cancer progression, and death toll were not significant ( P = .24, 0.24, 0.61, and 0.49, respectively) between the 2 groups. Multivariate analysis revealed that temporary discontinuation of therapy did not predict poor progress-free survival independently (hazard ratio = 1.007, 95% confidence interval: 0.653–1.552, P = .98). For patients in geographical regions with a high risk for COVID-19 infections, temporarily suspending treatment for late-stage non–small cell lung cancer patients is not likely to significantly impact their prognosis if they can return to treatment within 3 months of discontinuation.